FCC or HCP: The stable close-packed lattice of crystallographically equivalent spherical micelles in block copolymer/homopolymer blend. (15th April 2019) - Chen, Li-Ting; Chen, Chun-Yu; Chen, Hsin-Lung
Abstract: Spherical micelles formed by block copolymers (bcps) are soft colloids capable of packing into three-dimensionally ordered lattice. Although close-packed sphere structure has been predicted to exist over a narrow region in the phase diagram, it remains unclear whether face-centered cubic (FCC) or hexagonal close packed (HCP) lattice is the stable close packing symmetry for the crystallographically equivalent bcp micelles, as they are essentially degenerated. The present study explores the lattice structure organized by the spherical micelles in bcp/homopolymer blends after erasing the solvent history involved in the blend preparation. The facts that the FCC structure developed in the solvent-cast blend transformed into HCP on heating and HCP phase was formed upon cooling from the disordered micelle phase attest that HCP was the favored close-packed lattice over FCC. The better thermodynamic stability of HCP phase was attributed to the more extensive connectivity of the octahedron voids in the lattice, which prescribed a higher overall translational entropy of the homopolymer chains localized in the voids for space filling. Graphical abstract: Image 1 Highlights: Spherical micelles formed by block copolymers can pack into 3D ordered lattice. FCC and HCP are the two generic types of close-packed lattices. HCP is favored over FCC for micelles formed by block copolymer/homopolymer blend. Connectivity of octahedron voids in lattice prescribes the better stability of HCP.